DEVELOPMENT OF GLUTEN-FREE COMPOSITE FLOUR BLENDS - Quiñones, Renissa R; Macachor, Corazon P; Quinoñes, Hubert G. (Journal of Agriculture and Technology Management, 2018)
People with celiac disease depend on gluten-free foods to maintain quality of life. This study aimed to determine the physico-chemical and organoleptic properties of gluten-free composite flour blends for celiac disease patients utilizing different percentage composition of rice flour, potato starch, cassava starch, millet flour and corn flour. The experimental design was laid out in the study with six (6) treatments in three (3) replications using Completely Randomized Design (CRD) under controlled condition. The experimental samples were subjected to different laboratory analyses. Sensory evaluation of the control and gluten-free treatments had revealed that there were no significant mean differences among treatments in all of the sensory characteristics. However, gluten-free flour blend (T2) had higher level of acceptance as compared to other gluten-free flour blend treatments. The composite gluten-free flour blends had 0 percent crude gluten. Utilizing available novel/functional ingredients can produce gluten -free composite flour with a comparable sensory characteristics and nutritional quality except protein content with  the  commercially  wheat  flours.  Hence,  it  is  recommended  for  the  use  of  gluten -free composite flour blends for food and pharmaceutical uses.